Hygrophorus aurantiosquamosus (Hygrophoraceae, Agaricales), a new species of Hygrophorus section Chrysodontes from western China - Huang, Hong-Yan; Zhang, Wen-Hao; Huang, Ting; Tang, Li-Ping (Phytotaxa, 2021)
In China, the European species, Hygrophorus chrysodon, is widely reported in western and northeastern provinces. After carefully comparing H. chrysodon from China and Europe, we found that the European and Chinese materials were different lineages in molecular trees, and there were also obvious differences in morphology between the two lineages. The evidence from morphology and phylogeny indicated that the presence of H. chrysodon in China is doubtful and that the Chinese material represents an undescribed species. Thus, H. aurantiosquamosus is proposed as a new species. This new taxon is characterized by its yellowish white pileus covered with golden yellow squamules, a stipe concolorous with the pileus and covered with yellow floccules, a distinct pileipellis composed of narrow hyphae with inflated terminal elements of various shapes (clavate, cylindrical, lacrymoid to subglobose), and elongate to subcylindrical basidiospores measuring 9.5–12 × 4–5.5 μm. The new species occurs in Picea forests at high elevations of western China, such as Qinghai, Sichuan, and Tibet provinces.